A COMPENDIOUS NARRATION OF POST-INDEPENDENT HOLOCAUST IN BAPSI SIDHWA’S ICE-CANDY-MAN (International Journal of Food and Nutritional Sciences, 2022)
BapsiSidhwa is a reputed Pakistani-American novelist who has probed deep into the social, religious and political turmoil that took place immediately after the partition of India and exposed the impact of the same in her novel Ice-Candy-Man. The novel is highly satirical in tone. It delineates the Hindu-Muslim conflict that has distorted and uprooted the communal harmony and peace. She also brings to limelight the reasons for the conversion of Hindus to Islam and Christianity. It is to save themselves from being brutally killed or forcefully abducted or raped. Sidhwacriticises the British for colonising India and enslaving the countrymen for maintaining and exercising their imperial rule. She also raises her voice against the social evils such as rape, murder, physical assault, child marriage, women trafficking, prostitution and forceful migration. On the other hand, Sidhwa is all in praise for the Parsi community who have respected the social and the religious system of the Indians and in addition, they have never attempted to convert the natives to embrace their religious doctrines. Sidhwa mocks at the politicians who have been responsible for the Partition of India (1947) which had resulted in horrible genocide. The research paper is an attempt to explore and expose the humiliation and exploitation encountered by the Indians during the Partition of India.